2006
DOI: 10.1007/s00264-006-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome of non-displaced fractures of the base of the fifth metatarsal

Abstract: The purpose of this study was to identify those factors that influence the outcome after conservative treatment of undisplaced fractures of the fifth metatarsal. This was done with univariate analyses and, for the first time, with regression analyses of day-to-day clinical practice. Thirty-eight patients were treated with plaster and periods of no weight bearing (NWB). Their mean age was 48 years. They were evaluated using the Olerud ankle score, with analogue scales for pain and comfort, and with questions ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…There are many descriptions of the types of fracture that affect the proximal end of the fifth metatarsal, but it seems clear that, with the exception of a true Jones fracture, the type of fracture has no influence on functional outcome. 9,17,[20][21][22] Most unite within eight weeks: those that do not are often asymptomatic. 23 Vorlat, Achtergael and Haentjens 22 reported that the most significant predictor of a poor functional outcome after these injuries was a prolonged period of non-weight-bearing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many descriptions of the types of fracture that affect the proximal end of the fifth metatarsal, but it seems clear that, with the exception of a true Jones fracture, the type of fracture has no influence on functional outcome. 9,17,[20][21][22] Most unite within eight weeks: those that do not are often asymptomatic. 23 Vorlat, Achtergael and Haentjens 22 reported that the most significant predictor of a poor functional outcome after these injuries was a prolonged period of non-weight-bearing.…”
Section: Discussionmentioning
confidence: 99%
“…9,17,[20][21][22] Most unite within eight weeks: those that do not are often asymptomatic. 23 Vorlat, Achtergael and Haentjens 22 reported that the most significant predictor of a poor functional outcome after these injuries was a prolonged period of non-weight-bearing. Despite a general acceptance that non-operative treatment gives a high rate of patient satisfaction, evidence about the best form of nonoperative treatment is scant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 187 tuberosity avulsion fractures from four studies in 2011 showed that there was no significant difference in union and refracture rates between different conservative treatment modalities (17). However, studies have shown that functional treatments with early weight bearing provide better functional outcome and earlier return to work than treatment by short leg cast with non-weight bearing walking (18-21). Therefore, functional treatments with orthopedic shoe, Jones bandage dressing or elastic bandage dressing are recommended.…”
Section: Resultsmentioning
confidence: 99%
“…9 Although tuberosity avulsion fractures tend to heal with nonoperative management, numerous studies have shown that healing of meta-diaphyseal fractures is somewhat less predictable, especially in active individuals and highly competitive athletes. 5,8,10,13,23,24 To evaluate the outcomes of treatment of these injuries in highly competitive athletes, Low et al 10 identified 83 meta-diaphyseal fifth metatarsal fractures in football players participating in the National Football League (NFL) Scouting Combine between 1988 and 2002. Of the 46 fractures treated operatively, there were 3 nonunions (6.5%).…”
Section: Discussionmentioning
confidence: 99%